2023
DOI: 10.7759/cureus.34475
|View full text |Cite
|
Sign up to set email alerts
|

Optimal Use of Advanced Practice Providers at an Academic Medical Center: A First-Year Retrospective Review

Abstract: Background Physician assistants/associates (PAs) and nurse practitioners (NPs), together known as advanced practice providers (APPs), practice with a high degree of clinical autonomy and professional respect, and play a critical role in team-based care. Aligning APP care delivery models to promote top-of-license practice is essential to improving ambulatory capacity and bottom-line expectations at academic medical centers (AMCs) in the 21 st century and beyond. This administra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(14 citation statements)
references
References 14 publications
0
1
0
Order By: Relevance
“…Nevertheless, the findings demonstrate the versatility inherent in the APP role as these providers are uniquely qualified to address the specific needs of patients. In fact, emerging data demonstrate that utilizing APPs to top-of license improves bottom-line expectations, patient access, patient satisfaction, and provider engagement without jeopardizing physician productivity [ 2 , 3 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, the findings demonstrate the versatility inherent in the APP role as these providers are uniquely qualified to address the specific needs of patients. In fact, emerging data demonstrate that utilizing APPs to top-of license improves bottom-line expectations, patient access, patient satisfaction, and provider engagement without jeopardizing physician productivity [ 2 , 3 ].…”
Section: Discussionmentioning
confidence: 99%
“…Physician assistants/associates (PAs) and nurse practitioners (NPs) collectively known as advanced practice providers (APPs) practice in all 50 states and in a variety of different specialties within the United States and abroad. Although there are differences in certification, educational philosophy, and licensure, both NPs and PAs perform overlapping responsibilities in the clinical setting, including billing for both clinical and procedural services [1][2][3][4][5]. With regard to hospital inpatient billing, APPs and physicians treating patients jointly have been subject to split/shared billing rules since October 2002; however, the Centers for Medicare and Medicaid Services (CMS) recently made substantive modifications to their split/shared evaluation and management (E/M) visit policy.…”
Section: Introductionmentioning
confidence: 99%
“…Previously published reports have outlined successes in optimizing the use of APPs in ambulatory clinics. 3,4 Such studies offer critical takeaways such as ensuring that all members of the care team are working at the top of their licenses (not just APPs, but also physicians, nurses, etc) and that financial incentives appropriately align. However, replicating these exact models in a different practice environment is not guaranteed to yield the same successful results, as the ideal urologist-APP health care delivery model will likely be heavily influenced by the unique clinical practice environment, available resources, and provider comfort.…”
Section: Editorial Commentarymentioning
confidence: 99%
“…14 While this is a single site, it offers the potential within directed process improvement initiatives to demonstrate the financial and patient access opportunities that can be realized by APP infrastructure investment. 15 : UC Irvine conducted a 1-year retrospective review of 220 APPs after the strategic implementation of an APP oversight committee. 15 The university reported that the critical first step of the oversight committee was implementing an APP director to guide role clarity, credentialing, compliance, scope, and optimization, followed by a multidisciplinary engagement survey and consultant input recommending a new infrastructure strategy.…”
Section: Emory Healthcare 12mentioning
confidence: 99%
“…15 : UC Irvine conducted a 1-year retrospective review of 220 APPs after the strategic implementation of an APP oversight committee. 15 The university reported that the critical first step of the oversight committee was implementing an APP director to guide role clarity, credentialing, compliance, scope, and optimization, followed by a multidisciplinary engagement survey and consultant input recommending a new infrastructure strategy. The deployment strategy had 3 major tactics: 1) Create an interprofessional APP oversight committee to enhance expectations, evaluate APP funds flow options, and monitor the deployment of standards across the enterprise, 2) Set ambulatory practice standards, which included a 36-hour patient-facing minimum and implement independent templates and equivalent practice support to remove shared visits, level the supports providing the APPs measurable top-of-scope measurable professional activities, and 3) Implementing APP funds flow redesign with a shared responsibility between the enterprise and the departments.…”
Section: Emory Healthcare 12mentioning
confidence: 99%